The Effectiveness of Direct Cash Village Fund Program in 2021 - Aceng Ulumudin; Yagus Triana; Mulyaningsih Mulyaningsih; Gugun Geusan Akbar (Universitas Sultan Ageng Tirtayasa, 2022)
: The COVID-19 pandemic has become a global health problem and causes various problems in the social, educational, and economic fields. One form of effort made by the government in efforts to deal with the effects of COVID-19 in the village is the implementation of the Direct Cash Assistance Program, sourced from the Village Fund budget, but in its implementation there are still many problems related to effectiveness. In measuring effectiveness, three factors are used, including the accuracy of timing, whether the results of the analysis show that it is effective, and the accuracy in selecting the beneficiary families. The method used in this descriptive qualitative research is research that aims to describe and explain events and phenomena that occur in the field and present data in a systematic, factual, and accurate manner regarding the facts or phenomena that occur in the field. The results showed that the Village Fund Direct Cash Assistance Program had been running in accordance with the procedures set by the government and the accuracy of the targets, but there were still discrepancies in the information so that some people who should have received the assistance did not receive it. Meanwhile, obstacles to the distribution of Village Fund Direct Cash Assistance, including access to some villages, are difficult to reach, resulting in delays in distribution.